Pengembangan Media Self Trainning Basic Prenatal Yoga Berbasis Audiovisual di Puskesmas Pamulang Tangerang Selatan - Siti Dariyani; Reni Nofita; Mardi Yana (Indonesian Journal of Midwifery (IJM), 2021)
Pregnancy and childbirth are inseparable chain reactions in a normal woman's life. To undergo a safe and comfortable pregnancy, pregnant women must be able to manage their body, mind and spirit holistically during pregnancy. (Kuswandi,2013) Changes in the safety and comfort of pregnant women are closely related to physical and psychological changes. (Prawiroharjo,2015) To reduce the physical and psychological complaints of mothers during pregnancy, what can be done by including the mother in pregnancy exercise classes, Prenatal yoga is a type of exercise that is good for pregnant women to do. Practicing yoga means that pregnant women practice physical postures, breathing techniques, and meditation.Based on the data obtained at Pamulang Health Center, from 684 pregnant women during January to April, only 20% of pregnant women attended the pregnancy class provided by the puskesmas, the remaining 80% of pregnant women were not involved in gymnastics classes at all. The absence of pregnant women is due to busyness and unsuitable schedules. The general objective of this study is to develop audiovisual self-training media for basic prenatal yoga and to test its effectiveness.The research method is action research. The first stage will conduct a study of the condition and level of needs of pregnant women about basic prenatal yoga. The second stage will be the process of making audiovisual media for basic prenatal yoga self-training. The third stage is testing the effectiveness of the media. The results showed that 60% of respondents did not know well what Prenatal Yoga was, pre-intervention described the mean score of physiological comfort during pregnancy of 56.1 with a range of values ranging from a score of 35-77. The mean value obtained post intervention was 48.4 with scores ranging from 30-70. p value of 0,000. Thus, it is known that there is a significant relationship between prenatal yoga movements and physiological comfort during pregnancy.Â